2003
DOI: 10.1002/jnr.10868
|View full text |Cite
|
Sign up to set email alerts
|

Graded reoxygenation with chemical inhibition of oxidative phosphorylation improves posthypoxic recovery in murine hippocampal slices

Abstract: Rapid and complete tissue reoxygenation is a prime goal of present stroke therapy. However, reoxygenation may trigger detrimental cascades that partially antagonize beneficial effects. It was our goal to investigate selective grading of reoxygenation with targeting of single mitochondrial complexes in murine hippocampal slices. Population spike amplitude (PSAP) and NADH were measured during hypoxic hypoxia (15 min) and recovery (45 min). With onset of reoxygenation, slices were treated for different times with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In our study, in opposite to the mice with inhibited C-I, the mice with inhibited C-II demonstrated exacerbation of HI brain injury, suggesting the priority of FAD-linked over NAD-linked phosphorylation in the brain recovery. An inhibition of C-I with amytal significantly prolonged recovery of NADH oxidation in murine hippocampal slices during reperfusion, yet the functional (population spike amplitude) recovery was improved compared to controls (Huber et al, 2004). …”
Section: Discussionmentioning
confidence: 92%
“…In our study, in opposite to the mice with inhibited C-I, the mice with inhibited C-II demonstrated exacerbation of HI brain injury, suggesting the priority of FAD-linked over NAD-linked phosphorylation in the brain recovery. An inhibition of C-I with amytal significantly prolonged recovery of NADH oxidation in murine hippocampal slices during reperfusion, yet the functional (population spike amplitude) recovery was improved compared to controls (Huber et al, 2004). …”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have clearly demonstrated that brief, nonlethal episodes of ischemia can confer prophylaxis against subsequent stroke3,7 or myocardial infarction4,5, and studies in model systems have shown that chemical inhibition of mitochondrial respiration can mimic this protection, a process coined “chemical preconditioning”6. Having shown that meclizine, an over-the-counter drug that crosses the blood brain barrier can gently silence respiration, we sought to determine whether this drug is cardioprotective and neuroprotective in cellular and animal models.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of literature demonstrates that agents that blunt respiration can offer prophylaxis against cell death following ischemia and reperfusion in the heart4,5,27 or brain3,6,26. This effect is thought to occur via suppression of oxidative injury and cell-death and may be related to protection conferred by ischemic preconditioning, though the precise molecular mechanism is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third pathway -Warburg pentose-cycle or pentose phosphate pathway (hexose monophosphate shunt) -represents direct oxidation in cytosol and provides more energy but is slower compared to glycolysis. The switch from the first to the third energy production pathway may be done by using sodium oxybutirate and gamma-hydroxybutyrate, serotonin (mexamin), barbiturates, venotropic drugs and phenotiasin [86,[92][93][94][95][96]. The switch of cellular energy metabolism from the third to the first pathway may be forced by insulin, application of which in combination with glucose and potassium may be beneficial under the situation when immediate energy production is required [97].…”
Section: Paas That Switch the Pathways Of Cellular Energy Metabolismmentioning
confidence: 99%